A selection of grapes from Sardinia: antioxidant properties - Loru, D.; Diena, M.; Incani, et al., A. (Progress in Nutrition, 2013)
Several studies have suggested that grape extracts possess different biological actions and may be beneficial in the prevention of many human diseases, associated with oxidative stress; however rather scarce data on the biological properties of the countless varieties of grapes growing in Sardinia are available. Grape and wine extracts are known to contain high levels of polyphenolic compounds. Polyphenols have been proposed to exert beneficial effects in a multitude of disease states, including cancer, cardiovascular diseases and neurodegenerative disorders. Many of the biological actions of polyphenols have been attributed to their antioxidant properties. In the present study we investigated the antioxidant effect of extracts from 6 varieties of grape growing in Sardinia (Cannonau, Cabernet-sauvignon, Malvasia, Vermentino, Chardonnay, Sauvignon), in simple in vitro systems, during autoxidation of linoleic acid at 37°C and during cholesterol oxidation at 140°C, in the absence of solvent. The cytotoxicity and the capacity of grape extracts to inhibit MDA production were evaluated in the human colon adenocarcinoma cell line, Caco-2. This cell line spontaneously undergoes full differentiation in vitro with enterocyte-like features and has been recognized as a suitable model for evaluating the effect of nutrient components. All tested grape extracts showed no cytotoxicity in the range 25-100 μg/ml and showed a significant antioxidant activity, beeing the native grape extracts from Sardinia the most active. Selezione di uve dalla Sardegna: proprietà antiossidanti Numerosi studi hanno messo in evidenza che l’estratto di uva possiede diverse proprietà biologiche che possono essere importanti nella prevenzione delle patologie associate allo stress ossidativo; sono però scarsi i dati sulle proprietà biologiche delle innumerevoli varietà di uve che crescono in Sardegna. Gli estratti di uva e di vino sono noti per contenere elevate concentrazioni di composti polifenolici. Ai polifenoli sono stati ascritti numerosi effetti benefici in differenti stati patologici, tra cui tumori, patologie cardiovascolari e neurodegenerative. Molte delle azioni biologiche dei polifenoli sono state attribuite alle loro proprietà antiossidanti. In questo lavoro abbiamo valutato l’effetto antiossidante degli estratti di 6 varietà di uva coltivate in Sardegna (Cannonau, Cabernetsauvignon, Malvasia, Vermentino, Chardonnay, Sauvignon), in semplici sistemi in vitro, durante l’autossidazione dell’acido linoleico a 37°C e durante l’ossidazione del colesterolo a 140°C, in assenza di solvente. La citotossicità e la capacità degli estratti di uva di inibire la produzione di MDA sono state valutate in cellule umane di adenocarcinoma di colon, Caco-2. Questa linea cellulare, in vitro, subisce spontaneamente una completa differenziazione, assumendo le caratteristiche degli enterociti ed è stata riconosciuta come un modello adatto per valutare l’effetto dei componenti nutrizionali. Tutti gli estratti di uva testati non hanno mostrato citotossicità nel range di 25-100 μg/ml e hanno mostrato una significativa attività antiossidante, gli estratti delle uve tipiche della Sardegna hanno mostrato la maggiore attività.